Pengembangan Materi Menulis Teks Deskripsi Siswa Menggunakan Model Mind Mapping - Erlisa Kambera Nauli Lumban Tobing; Oky Fardian Gafari (Jurnal Riset Rumpun Ilmu Bahasa, 2023)
This study aims to: 1) develop material for writing descriptive texts using a mind mapping model in Indonesian subjects; 2) analyze the feasibility of writing descriptive text material using the mind mapping model as teaching material in Indonesian language lessons in class VII junior high school. The development method used is the research and development method from Borg and Gall modified by Sugiyono with five stages. The development stages include analyzing potential and problems, collecting data, designing product development, validating, and revising products. The development was validated by two validators, namely material experts with an assessment reaching 86% included in the very feasible category, media expert validation with an assessment reaching 74% included in the feasible category. From the overall feasibility assessment of the teaching materials that have been presented, the descriptive text teaching materials using the Mind Mapping model for class VII have decent quality and can be accepted as one of the teaching materials.